La identidad en el plato. El camino identitario argentino a través de sus alimentos. - MAGNANI, ILARIA (Scripta)
Along with the fundamental material function that it performs, the symbolic value of food is well known, capable of harboring cultural, affective, and identity meanings -either at a personal or a national level-. These themes and their historical implications are emphasized by scholars such as Montanari and Flandrin, among others. Based on these considerations, I propose to trace the description of Argentine food traditions to delineate their representation in relation to the nascent national identity, observe their modifications and analyze the meanings that they entail. To this end I will base myself on a corpus made up of: José Antonio Wilde, Buenos Aires desde setenta años atrás (1881); Domingo Faustino Sarmiento, Recuerdos de provincia (1850); Lucio Mansillas, Mis memorias (1904) y Una excursión a los indios ranqueles (1870).